“This Board Has a Duty to Intervene”: Challenging the Spadina Expressway through the Ontario Municipal Board, 1963–1971 - Milligan, Ian (Urban History Review / Revue d'histoire urbaine, 2011)
This article examines the pivotal role played by the unelected Ontario Municipal Board (OMB) in the opposition to the Spadina Expressway, from initial proposals in 1963 to the expressway’s 1971 cancellation by the provincial government. After considerable grassroots protests, the matter came to a head in a full OMB hearing in late 1970. There, the OMB had to balance majority interests—as expressed by Metro Council, strongly in favour of the project—versus minority interests of community activists, residents in the path of the expressway, and a growing international network of expressway opponents. Indeed, because the scope of the OMB’s mandate was wide, it was able to study the effects of expressways elsewhere in North America. While the OMB eventually voted in favour of the expressway, this was the first non-unanimous decision in its long history. Chairman Joseph Kennedy’s dissenting opinion stood up for minority rights, set the stage for a debate on the role of the OMB in municipal planning and governance, and made it palatable, legitimate, and respectable for the Ontario premier to cancel the expressway four months later. This article also discusses the OMB more generally, exploring its significance in light of continuing municipal debates surrounding the role of unelected land use tribunals versus local governments.